Testing of Banking Services in Bangladesh: A Study on Prime Bank Limited Rangpur Branch - Hossain, Md. Zahid; Quddus, Md. Tareque (Asian Business Review, 2015)
Customer satisfaction is asset .At present clients are so much conscious and sensitive about the services what they receive. The study focused on testing of banking services in Bangladesh to know the gap between customer expectation and customer satisfaction. Findings of the study clearly suggest that clients are overall satisfied, and their attitude is very positive towards Prime Bank Limited Rangpur Branch. It also shows that they are not delighted with existing services. The study recommends putting more attention for the services, providing something new to the customers to gain competitive advantage and have an impact for a long time and help developing the sector with a fair competitive environment.